Harvesting Ornamental Fish From Ponds - Tina C. Crosby; Jeffrey E. Hill; Carlos V. Martinez; Craig A. Watson; Roy P. Yanong (EDIS)
FA-117, 6-page illustrated fact sheet by Tina C. Crosby, Jeffrey E. Hill, Carlos V. Martinez, Craig A. Watson, and Roy P.E. Yanong, describes two methods of collecting fish from earthen ponds, trapping and seining, and the advantages and disadvantages of each. Includes recommended reading list. Published by the UF Department of Fisheries and Aquatic Sciences, November 2006.